2023
DOI: 10.1128/spectrum.00378-23
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Inhibits NRF2-Mediated Antioxidant Responses in Airway Epithelial Cells and in the Lung of a Murine Model of Infection

Abstract: The antioxidant defense system plays a major function in protecting the organism against oxidative damage caused by free radicals. COVID-19 patients often present with biochemical characteristics of uncontrolled pro-oxidative responses in the respiratory tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 64 publications
3
16
0
Order By: Relevance
“…To characterize the role of NRF2 during SARS-CoV-2 infection, we performed transcriptomic analyses that did not evidence modulation of expression of genes linked to the NRF2 pathway in SARS-CoV-2 infected Calu-3 cells 36 hours after infection. This result extends a previous study that reported decreased NRF2 protein levels at 48 hours but not 24 hours after infection of Calu-3 cells[11] and is in accordance with the repression of the NRF2 pathway in COVID-19 patient lung biopsies[7]. Altogether, these results suggest that decreased levels of NRF2 is a late event during SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To characterize the role of NRF2 during SARS-CoV-2 infection, we performed transcriptomic analyses that did not evidence modulation of expression of genes linked to the NRF2 pathway in SARS-CoV-2 infected Calu-3 cells 36 hours after infection. This result extends a previous study that reported decreased NRF2 protein levels at 48 hours but not 24 hours after infection of Calu-3 cells[11] and is in accordance with the repression of the NRF2 pathway in COVID-19 patient lung biopsies[7]. Altogether, these results suggest that decreased levels of NRF2 is a late event during SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance, analyses of lung biopsies from COVID-19 patients show that genes regulated by NRF2 have a decreased mRNA levels[7] and expression of NRF2 protein is decreased in children infected with SARS-CoV-2[8]. Furthermore, the NSP14 protein of SARS-CoV-2 impairs NRF2/HMOX1 activation[9], the SARS-CoV-2 ORF3a positively regulates ferroptosis by degradation of NRF2[10] and SARS-CoV-2 directly inhibits NRF2-mediated antioxidant response[11]. Interestingly, SARS-CoV-2 replication does not seem to be dependent on the Keap1/Nrf2 pathway but the pathogenic consequences of SARS-CoV-2 infection depend on the Keap1/Nrf2 pathway[11].…”
Section: Introductionmentioning
confidence: 99%
“…The induction of Nrf2 in TGEV-infected cells in vitro was shown by Wang et al [32]. It should be mentioned that in case of SARS-CoV-2, strong inhibition of Nrf2 in the lungs was demonstrated at the late stages of infection [33,34].…”
Section: Discussionmentioning
confidence: 87%
“…Similar to our findings in this work, adult Nrf2 KO mice on the ICR background [ 33 ] or older mice on a BL6 background were shown to have increased RSV and hMPV peak replication and shedding [ 24 ]. We also found increased SARS-CoV-2 replication in BALB/c Nrf2 KO mice compared to WT controls [ 20 ]. We proposed several different possibilities to explain such findings, including: (1) A relative defect in the antioxidant defense system and enhanced oxidative response in the absence of Nrf2, supported by evidence that exogenous treatment of cells or mice with antioxidant enzymes or synthetic compounds with antioxidant activity reduces the replication/viral load [ 25 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some viral infections have been shown to activate Nrf2, among them hepatitis B and C viruses, human cytomegalovirus, Kaposi’s sarcoma-associated herpes virus and Marburg virus [ 13 , 14 , 15 , 16 , 17 , 18 ], respiratory viruses, including RSV, hMPV, influenza and SARS-CoV-2 are associated with a progressive reduction in Nrf2 cellular levels and subsequent inhibition of AOE expression [ 7 , 19 , 20 ]. Indeed, the Nrf2 pathway has been shown to play a protective role in the murine airways against RSV-induced acute lung injury and oxidative stress: more severe RSV disease, including higher peak viral titers, augmented inflammation and enhanced disease were found in Nrf2 KO mice compared to Nrf2-competent mice [ 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%